The Lebanese and the Syrian within the French Empire : transnational migrations in colonial and independence contexts : Lebanon, Syria – French West Africa, 1890s-1960s - (:unkn) unknown (My University, 2021)
Inspired by Imperial Studies and connected history, this PhD reseach aims at studying chain migration between Lebanon and Syria and French colonial West Africa from the 1890s to the 1960s afterwards. It seeks to illuminate the migration networks and their evolution mostly from the French Imperial power point of view through French colonial and Foreign Minister's archives. This research will also pay attention to all the internal and external actors involved in this migration and migrants' integration in French colonial West African society and economy. Through the study of chain migration between Lebanon and Syria to West Africa, we also aim at stressing all the means French imperial power implemented to frame migrants' mobility and activities in order to maintain the frame of French Empire all along political changes in the Middle East and in Africa up to formal decolonization in 1960.
Keywords: African Research